Impact of human capital, FDI on economic growth: Empirical evidence from MENA region - Oussama, RITAHI; Abdellah, ECHAOUI; Abdelouahad, ES-SABIR (Asian Development Policy Review, 2025)
This study investigates the short- and long-term effects of foreign direct investment (FDI), human capital, capital formation, domestic credit, and inflation on GDP in a panel of MENA countries. It also explores how human capital moderates the impact of FDI on economic growth. Using panel data from 16 MENA countries spanning 1990–2023, the study employs the Cross-Sectionally Augmented Autoregressive Distributed Lag (CS-ARDL) model to account for heterogeneity and cross-sectional dependence. Human capital and capital formation have significant positive effects on GDP in both the short and long term. While FDI alone has no significant impact, its interaction with human capital shows a marginally positive effect. Domestic credit slightly hinders growth, and inflation yields mixed results. The findings highlight the essential role of human capital in enhancing the growth benefits of FDI and strengthening long-term economic performance through structural investment. Policymakers should prioritize education and human capital development to fully leverage FDI. Integrated strategies that strengthen institutional readiness and absorptive capacity are key to achieving sustainable growth in the MENA region.